(untitled) (Research, Society and Development, 2020)
This study aims to discuss the presence of Environmental Education in Elementary Education in Brazil considering the National Common Curriculum Base and its recommendation for the area of Humanities specifically Geography. Thus, the research considered work of authors such as Limaverde (2015), Lopes (2013), Macedo (2014) and Tonegutti (2019). As for legal framework, the 1988 Brazilian Federal Constitution as well as Law number 9,394, December 20th -1996 that deals with the Brazilian Law of Directives and Bases and Law number 9.795, of April 27th of 1999 that deals with the Brazilian Policy of Environmental Education were considered. Environmental Education emerged in the Brazilian elementary school curriculum through the National Curriculum Parameters in the 1990s by means of cross cutting themes including Labor, Environment and Consumption. It was seen that Environmental Education is mentioned in the National Common Curriculum Base for elementary or high school. Although the issue is restricted to current legislation, there is no expression of its fundamentals. It was also perceived that presented content and skills are under explored. Thus, it is considered that there is a waste regarding the potential for conceptual and methodological conception, especially related to the principle of interdisciplinarity, seen through the integration of cross cutting issues in the explored themes. Therefore, it is the teacher´s responsibility to correct this asymmetry between Environmental Education legislation and the elementary education curriculum, whether in initial or continued phases incisively thorough education. Thus, instead of advancing the curricular issue for the area of Environmental Education, the referred document is a setback.